Formulation of a "Legal and judical reform strategy for Cambodia" - Siphana, Sok (Cambodia Legal Resources Development Center (CLRDC), 2002)
Cambodia's success will mean liberation: liberation from hunger, poverty and income constraints, liberation from ignorance, and liberation from fear, especially from the fear of dying when still young. In the words of Nobel laureate Amartya Sen "...economic growth, which brings about a high standard of living, is interpreted too often in materialistic terms. But we need to pay attention to its human aspect too. For developing countries and LDCs alike, economic growth should be looked at as an effective force of liberation."